Kálmán Barsy, un escritor húngaro en Puerto Rico - Laboncz, Zsuzsa (Acta Hispanica, 2012)
The name of this Hungarian-born, l^atin American writer may sound unfamiliar to us,Hungarian readers, but nowadays Kálmán Barsy is one of the most popular and highlyrecognised authors in America, whose very first novel was honored with the pri^e Casa de lasAméricas in 1982. His novels, short stories and essays have been published in severallanguages, but we can only read one of them in Hungarian. No doubt, this work occupies avery important place in our literature, as it is treating a less known subject, the story of the socalledsecond generation of the emigration. This second generation has only a few members likeKálmán Barsy, who shares his homeland memories, and the difficulties of the integration into anew and strange community. With this study I try to present not just his life and work, butalso the way he describes the experience of an emigrant of the second generation.